Dipole and Gausson soliton for ultrashort laser pulse with high order dispersion. (September 2017) - Ashraf, R.; Ahmad, M.O.; Younis, M.; Ali, K.; Rizvi, S.T.R.
Abstract: In this paper, we find the dipole soliton (dark-in-the bright) for higher order nonlinear Schrödinger equation (HNLSE) with kerr law. This equation represents the propagation of a nonlinear ultrashort laser pulse in the optical fiber. We use the ansatz method of Choudhuri and Porsezian to find the solitary wave solution, which is combination of product of dark and bright solitary waves. We also find single Gausson soliton solution for (HNLSE) with log law nonlinearity described in optical nano fibers. Highlights: In this paper, we find the dipole solitons or dark in the bright soliton solutions of the higher order nonlinear Schrodinger equation(HNLSE), using the solitary wave ansatz method. Some constraint conditions are placed in order for the solitons to exist. We also obtained the exact Gausson solution for HNLSE. Here, ansatz method is used to carry out the integration of the extended form of HNLSE. A couple of conserved quantities are also calculated for HNLSE using Gausson solution.